Grain in a Plasma in the Presence of External Electric Field: Kinetic Calculation of Effective Potential and Ionic Drag Force - Zagorodny, A.G.; Rogal, I.V.; Momot, A.I.; Schweigert, I.V. (Відділення фізики і астрономії НАН України, 2010)
Kinetic calculations of the effective grain potential are presented for the case of weakly-ionized plasma in the external electric field. The drag force associated with the ionic drift in the external field is found. It is shown that the absorption of electrons and ions by the grain can cause the change of the direction of the drag force. Представлено кiнетичнi розрахунки ефективного потенцiалу порошинки для випадку слабоiонiзованої плазми у зовнiшньому електричному полi. Знайдено силу опору, яка пов’язана з дрейфом iонiв у зовнiшньому полi. Показано, що поглинання електронiв та iонiв порошинкою може привести до змiни напрямку сили опору.